Development of a standardized chart review method to identify drug‐related hospital admissions in older people. (17th August 2018) - Thevelin, Stefanie; Spinewine, Anne; Beuscart, Jean‐Baptiste; Boland, Benoit; Marien, Sophie; Vaillant, Fanny; Wilting, Ingeborg; Vondeling, Ariel; Floriani, Carmen; Schneider, Claudio; Donzé, Jacques; Rodondi, Nicolas; et al.
Abstract : Aims: We aimed to develop a standardized chart review method to identify drug‐related hospital admissions (DRA) in older people caused by non‐preventable adverse drug reactions and preventable medication errors including overuse, underuse and misuse of medications: the DRA adjudication guide. Methods: The DRA adjudication guide was developed based on design and test iterations with international and multidisciplinary input in four subsequent steps: literature review; evaluation of content validity using a Delphi consensus technique; a pilot test; and a reliability study. Results: The DRA adjudication guide provides definitions, examples and step‐by‐step instructions to measure DRA. A three‐step standardized chart review method was elaborated including: (i) data abstraction; (ii) explicit screening with a newly developed trigger tool for DRA in older people; and (iii) consensus adjudication for causality by a pharmacist and a physician using the World Health Organization‐Uppsala Monitoring Centre and Hallas criteria. A 15‐member international Delphi panel reached consensus agreement on 26 triggers for DRA in older people. The DRA adjudication guide showed good feasibility of use and achieved moderate inter‐rater reliability for the evaluation of 16 cases by four European adjudication pairs (71% agreement, κ = 0.41). Disagreements arose mainly for cases with potential underuse. Conclusions: The DRA adjudication guide is the first standardized chart review method to identify DRA in older persons. Content validity, feasibility of use and inter‐rater reliability were found to be satisfactory. The method can be used as an outcome measure for interventions targeted at improving quality and safety of medication use in older people.